Evaluation of the Classification of the Type A Terminal in Leuwipanjang, Bandung - Hendry Sampurna; Ike Oktaviani; Ngir Tjuk Hirwo; Draga Hasan Saputra; Jon Putra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
These changes impact terminal classification, service quality, and overall terminal performance. Terminal class determination is based on Decree No. 6251 of 2017, while service and performance assessments are measured using the Importance Performance Analysis (IPA) method. The analysis results indicate that aspects falling into quadrants I and II are the top priority for improvement, while aspects in quadrants III and IV do not require immediate improvement. Terminal classification is determined through field observations based on five indicators that align with existing conditions. Performance evaluation is conducted based on Minister of Transportation Regulation No. 24 of 2021 concerning the implementation of road passenger terminals. The results indicate that Leuwipanjang Terminal falls into class 2 and requires adjustments to several indicators, such as transportation needs, starting and destination points, number of routes, and number of staff. Furthermore, several performance aspects require improvement, such as workforce capabilities, cleanliness and utilization of primary and supporting facilities, technology implementation, and matters related to safety, security, and smooth traffic flow.